Saturday

December 3, 2016
Posted by **Haley** on Wednesday, March 14, 2012 at 11:30pm.

cos^4 theta- sin ^4 thetaover sin squared theta cos squared theta =cot squared theta - tan squared theta

- math -
**Steve**, Thursday, March 15, 2012 at 11:24amI'll use x for theta, for my convenience.

(cos^4x - sin^4x)/sin^2x cos^2x

= (cos^2x - sin^2x)(cos^2x + sin^2x)/sin^2x cos^2x

= (cos^2x - sin^2x)/sin^2x * (cos^2x + sin^2x)/cos^2x

= (cot^2x - 1)(1+tan^2x)

= cot^2x - 1 + cot^2xtan^2x - tan^2x

= cot^2x - 1 + 1 - tan^2x

= cot^2x - tan^2x